Improving Self-Direction Among Vocational Students During On-the-Job Training Through Behavioral Psychoeducation - Ice Desvikayati; Nurfarhanah Nurfarhanah; Zadrian Ardi; Rezki Hariko; Yeni Karneli; Ramdani Ramdani (STAI Hubbulwathan Duri, 2026)
Navigating the transition from vocational education to industry requires robust self-direction, yet many students exhibit passive behaviors and anxiety during industrial work practices. This gap between structured schooling and industrial independence hinders work readiness. This study evaluated the effectiveness of behavioral-based psychoeducation in enhancing self-direction among learners. Employing a quantitative quasi-experimental design with a one-group pretest-posttest approach, the study involved 20 Grade XII Computer Network students at SMKN 6 Batam, selected via purposive sampling for moderate self-direction levels. Data were collected using a validated self-direction scale and analyzed using Wilcoxon Signed Ranks and N-Gain tests. Results demonstrated a significant improvement, with mean scores rising from 91.90 (moderate) to 129.80 (high). Wilcoxon test confirmed statistical significance (Z = -3.920, p = 0.000), while the N-Gain score of 0.94 indicated high intervention effectiveness. Findings suggest that behavioral-based psychoeducation, leveraging positive reinforcement and self-management, fosters student autonomy. Consequently, integrating psychological interventions into pre-internship preparation programs is crucial for bridging the school-industry gap. This research underscores the necessity of holistic support systems in vocational education to ensure students possess psychological resilience and directional clarity required for successful industrial adaptation and career stability in a competitive labor market. Thus, educators must prioritize mental readiness alongside technical skills to optimize outcomes.